Assessment of the Administration and Practice of Juvenile Justice System in Abuja, Nigeria - James, Godswill (Mediterranean Journal of Social Sciences, 2013)
No social group seems to bear the direct brunt of economic crises like children and young persons. Because of their vulnerablenature, some of them resort to different forms of deviant activities, which bring them in conflict with the law. As a result, there isa range of laws at the international and local levels which set standard practice as it concerns juvenile offenders. However, thepractice of juvenile justice system in Nigeria tends to be at variance with these laws. This study examines the practice ofjuvenile justice system in Nigeria, with the view to assessing the effort of government in the administration and control ofjuvenile delinquency in line with established standard in Federal Capital Territory, Abuja. The study used structuredquestionnaires to elicit information from the respondents. Findings reveal that there exist laws to protect the rights andconditions of juveniles, but these laws do not adequately conform to international standard. Juveniles are subjected to poorconditions in police and prison cells; they are poorly fed, subjected to verbal and physical abuses, and not separated from adultprisoners. The study concludes that Nigerian juvenile justice administration needs to be reviewed and properly coordinated toreflect international rules and standards for the treatment of juvenile offenders.